Heavy duty hand truck / Abdul Hadi Rosli ... [et al.] - Rosli, Abdul Hadi; Ishak, Muhammad Asyraf; Muhamad Ya Rafi, Muhammad Afif Syafieq; Mohd Shupian, Shamiem Farhan; Ahmad Hakhim, Ahmad Asyraf (2021)
The hand trolley is a very useful tool for moving loads from one position to another. However, its utility decreases when it needs to conquer such obstacles such as stairs or when it is used to transport small and circular shaped items, research is carried out in literature review to overcome these consequences based on types and mechanisms of stair climbing trolleys along with the optimum pulling force required to safely pull trolley, then three concepts of design were then generated on the basis of these results, from which Tri-Star wheel stair climbing trolley was selected as the most feasible concept. To stop small and circular form objects falling down during transportation due to their asymmetric shape, a bracket was added to the trolley. The design then runs through is CAE using Solidworks to produce simulations of trolleys when a load of 250 kg is added to it. Next, the hand trolley can also save space as it is designed to be folded on its body. with the advantage of being able to fold in the middle of the trolley body, this will also be used by users to lift the trolley and does not require a lot of manpower moreover it can also save time. The design was discussed and inferred on the basis of the results of the simulations. The design was discussed and inferred on the basis of the results of the simulations. In conclusion, hand trolley Tri-Star wheel stairclimbing will operate in satisfactory condition as it achieves the goals.